The Collaborative Roles of the Diagnostic Triad: Optometrists, Medical Laboratory Sciences, and Radiologists in Advancing Modern Healthcare Outcomes and Patient Safety - Hamad Nasser Abu Melhah, Mubarak Mohammed Mahdi Al Jafar, Faten Nasser Saeed Alqahtani, Mohammad Hussain Mohammad Al Dagrir, Salem Hamad Al Haider, Abdullah Mubarak Alnujaym, Ali Saleh Alshehri, Mohammed Futais Alhajri (Journal of International Crisis and Risk Communication Research, 2024)
The complexities of modern healthcare require a multidisciplinary approach to improve patient outcomes and ensure safety. This review explores the synergistic roles of ophthalmologists, medical laboratory scientists, and radiologists, referred to as the diagnostic triad, in enhancing diagnostic accuracy and healthcare efficiency. Integrating their expertise enables accurate diagnosis, personalized treatment, and optimized resource utilization. Despite the transformative potential of this collaboration, systemic challenges such as communication gaps and role ambiguity hinder their full realization. Solutions, including standardized protocols, advanced technologies, and multidisciplinary training, are proposed to improve collaborative workflows. Innovations such as artificial intelligence, big data analytics, and telehealth are amplifying the impact of the triad on modern healthcare.